ChemInform Abstract: Inverse Oxide/Metal Catalysts in Fundamental Studies and Practical Applications: A Perspective of Recent Developments. Issue 37 (August 2016) - Rodriguez, Jose A.; Liu, Ping; Graciani, Jesus; Senanayake, Sanjaya D.; Grinter, David C.; Stacchiola, Dario; Hrbek, Jan; Fernandez‐Sanz, Javier
Abstract: Review: 82 refs.